Pengaruh Konsentrasi Fenol terhadap Efektivitas Fotodegradasi Fenol menggunakan Komposit Titania-Carbon Nanotube (Surfaktan) - Desi Heltina; Nadhia Gasani Putri; Panca Setia Utama (Eksergi, 2020)
Aromatic compounds in industrial wastewater such as phenols can contribute as pollutants which are highly toxic and carcinogenic. Phenol degradation can be carried out by a photocatalytic process which can convert phenol into non-toxic and enviromentally friendly compounds. The performance of titania (TiO2) photocatalyst was enhanced by using carbon nanotube as a doping agent for titania. To reduce carbon nanotube agglomeration, the surface of carbon nanotube was modified with cocoPAS surfactant. The purpose of this study was to synthesize titania-carbon nanotube-cocoPAS composite and evaluated the effect of initial phenol concentration (10, 20, 30 ppm) on the phenol photodegradation effectivity using titania-carbon nanotube-cocoPAS composite. Titania-carbon nanotube-cocoPAS composite synthesis was carried out by forming a composite between TiO2 and carbon nanotube that had been modified by surfactant. Composite were characterized by SEM, FTIR, and XRD. Phenol photodegradation was carried out at a degradation temperature of 50ºC for 4 hours under UV light. Samples were drawn at regular intervals and residual concentration of phenol in each sample was analysed using UV-Visible spechtrophotometer. The highest degradation effectivity in 4 hours was 81% at initial phenol concentration of 10 ppm.